Evaluation of Quality and Stability of Fish-vegetable Composite Bio-silage based Fish Feed Stored at Room Temperature - Ghosh, Subal Kumar; Das, Rupali; Nayak, Binaya Bhusan; Xavier, K.A. Martin; Balange, Amjad K.; Nottanalan, Husain; Gore, Sandeep Bhaskar (International Journal of Bio-resource and Stress Management, 2024)
The present experiment was conducted during March–May 2022 at ICAR–CIFE, Mumbai, Maharashtra, India to develop a unique fish feed from locally available vegetable, and fish processing waste. These two sources of the waste were used in composite bio-silage (CBS) production by combining fish (80%)–vegetable (20%) waste with probiotic proteolytic strain (E. faecalis+L. acidophilus) and jaggery (15% Jaggery) as a carbon source. The final CBS materials were used in experimental fish feed preparation by replacing fish meal (FM) protein. Changes in physicochemical, and microbiological quality characteristics of fish feed were measured every 15th day at room temperature (25–30°C). There was no change in color, the appearance of a moderately bad odour, a little bit of soft texture, and broken pellets were found in the later stages of the storage. Crude protein (38.50–36.10%) and fat (8.60–4.82%) content were decreased whereas, moisture content increased (9.15–11.10%) in all samples during the storage period. There were no notable changes in ash or crude fiber. Lipid oxidation product TBARs (8.0–13.205 MDA; nmol mg-1), Total Plate Count (2.75–6.70 log cfu g-1), and Fungal Count (1–2.50 log cfu g-1) were within acceptable range. The study’s findings indicated that composite bio-silage incorporated fish feed has a shelf life of up to 60th days and can be fed during this period. The study also suggested that manufactured fish feed should not be stored for more than two months, either in the place of production or at the farmer’s store.